1997
DOI: 10.1046/j.1423-0410.1997.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Depletion and Storage of Single‐Donor Platelet Concentrates

Abstract: There is no advantage in terms of improved quality for prestorage leuko-depletion of PCs. Taking into account the obvious disadvantages of filtration, such as platelet loss and increasing costs per transfusion, we conclude that pre- or post-storage filtration of single-donor PCs should be done only for patients who have a clear indication for the transfusion of leukocyte-poor blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…In this case, preSF of single–donor platelet apheresis improved the storage conditions thus leading to a more efficient use of TH. This is in contradiction to data presented recently on leukocyte depletion of single–donor platelet concentrates [28]. This discrepancy may be explained by the difference in WBC content at day 0 (one log more WBC per apheresis in our study as compared to that of Weisbach et al [28]) and by the different methods of preparation of single–donor PC in both studies, and also by the fact that the study of Weisbach et al [28]examined only 10 THs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this case, preSF of single–donor platelet apheresis improved the storage conditions thus leading to a more efficient use of TH. This is in contradiction to data presented recently on leukocyte depletion of single–donor platelet concentrates [28]. This discrepancy may be explained by the difference in WBC content at day 0 (one log more WBC per apheresis in our study as compared to that of Weisbach et al [28]) and by the different methods of preparation of single–donor PC in both studies, and also by the fact that the study of Weisbach et al [28]examined only 10 THs.…”
Section: Discussioncontrasting
confidence: 99%
“…These conclusions apply specifically to the Autopheresis C system with its high initial WBC content. They also argue for the promotion of the newer systems of plateletpheresis with lower WBC content [28, 30, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…The collection efficiency of the final system was slightly but significantly (2%) inferior to the standard procedure. The drop in platelet yield is much lower than the 10–81% platelet loss reported for fiber filtration [18, 19, 20, 21, 22, 23, 24, 25]. …”
Section: Discussionmentioning
confidence: 75%
“…This leukoreduction is usually done by filtration [17]. However, filtration leukoreduction of PC not onyl reduces the WBC count in the filtered product but also causes platelet losses of about 20% (10–81%) [18, 19, 20, 21, 22, 23]. It may even sacrifice the complete PC in the case of blocked filters [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] A literature search was also performed to identify studies that had reported ranges for the various test results performed on PLT products stored for 5 and/or 7 days. [15][16][17][18][19][20][21][22][23][24][25] The reported values in these studies were used as a reference range for comparative purposes.…”
Section: Laboratory Testingmentioning
confidence: 99%